TRADISI MEMINANG BIDAN SAMPAI TRADISI MANDI KE AIR PADA MASYARAKAT MELAYU KELURAHAN KERUMUTAN KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Sariyanti Sariyanti '; Ridwan Melay Ridwan Melay; Kamaruddin Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Tradition meminang bidan is a tradition and a willingness to ask for help bidan kampung to assist in the delivery. While the tradition of bathing water is a tradition of the family to pay debts and to cleanse bidan kampung, mothers and children who have been born of bad blood at birth. The tradition is the custom for generations (of ancestors) were still ongoing in the community. The purpose of this study is to propose a bidan kampung to know the tradition and the tradition of bathing water, to determine the procedures for proposing traditional bidan kampung and procedures of the tradition of bathing water, to know the tradition and the tradition of a bidan kampung to propose to the water, to find out the perception Young Mother of bidan kampung. The method used in this study is the historical method and qualitative method. Data were obtained from interviews and analyzed in its own language. The research site is in the village Kerumutan Kerumutan Pelalawan District. When the study started from the seminar proposal until the completion of the last revision of thesis writers. Data collection techniques used are observation, documentation, technical literature and interviews. The results of this study indicate that the traditional bidan kampung to propose to the tradition of bathing water has done to date. The continued development of epoch-making tradition and the tradition of a bidan kampung to propose to the water had been left by the community Kerumutan village. Based on the research tradition and the tradition of a bidan kampung to propose to the water should be one culture will be retained in order to continue this tradition into the next generation and is one of the cultural characteristics of Riau province.Keywords: Tradition, Meminang Bidan, Mandi ke Air